2018
DOI: 10.1183/13993003.02697-2017
|View full text |Cite
|
Sign up to set email alerts
|

Maximal exercise capacity in patients with obstructive sleep apnoea syndrome: a systematic review and meta-analysis

Abstract: Maximal aerobic capacity is a strong health predictor and peak oxygen consumption (') is considered a reflection of total body health. No systematic reviews or meta-analyses to date have synthesised the existing data regarding ' in patients with obstructive sleep apnoea (OSA).A systematic review of English and French articles using PubMed/MEDLINE and Embase included studies assessing ' in OSA patients either in mL·kg·min compared with controls or in % predicted. Two independent reviewers analysed the studies, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
30
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 69 publications
4
30
0
3
Order By: Relevance
“…Powell et al [28] studied exercise performance among military personnel with and without moderate-severe OSAS. The lack of significant differences among the two subgroups could be explained by the low average age in the OSAS and control groups (40.7 and 39.4, respectively) but also by the higher grade of habitual physical activity (characteristic for this population subset) [29].…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…Powell et al [28] studied exercise performance among military personnel with and without moderate-severe OSAS. The lack of significant differences among the two subgroups could be explained by the low average age in the OSAS and control groups (40.7 and 39.4, respectively) but also by the higher grade of habitual physical activity (characteristic for this population subset) [29].…”
Section: Discussionmentioning
confidence: 84%
“…Previous studies [24,25,29] reported that OSAS patients have higher DBP values and decreased HR recovery compared to controls. When analyzing the two apnea severity subgroups, we observed significantly higher baseline and AT-SBP values (but no significant differences regarding HR response during exercise) in the severe OSA subgroup.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…In this issue of the European Respiratory Journal, MENDELSON et al [11] report a systematic review and meta-analysis to clarify the possible alterations of V′O 2 peak in patients with OSA. When all relevant studies were compiled, the authors found that V′O 2 peak is significantly lower in OSA patients than proper controls (mean difference −2.7 mL•kg −1 •min −1 , 95% CI −4.0 to −1.4; p<0.001; n=850) and that mean±SD V′O 2 peak is 90.7±21.0% of predicted in OSA patients.…”
mentioning
confidence: 99%